Polyproline and the “spectroscopic ruler” revisited with single-molecule fluorescence - Benjamin Schuler; Everett A. Lipman; Peter Steinbach; Michael U. Kumke; William A. Eaton (2005)
To determine whether Förster resonance energy transfer (FRET) measurements can provide quantitative distance information in single-molecule fluorescence experiments on polypeptides, we measured FRET efficiency distributions for donor and acceptor dyes attached to the ends of freely diffusing polyproline molecules of various lengths. The observed mean FRET efficiencies agree with those determined from ensemble lifetime measurements but differ considerably from the values expected from Förster theory, with polyproline treated as a rigid rod. At donor–acceptor distances much less than the Förster radius R 0 , the observed efficiencies are lower than predicted, whereas at distances comparable to and greater than R 0 , they are much higher. Two possible contributions to the former are incomplete orientational averaging during the donor lifetime and, because of the large size of the dyes, breakdown of the point-dipole approximation assumed in Förster theory. End-to-end distance distributions and correlation times obtained from Langevin molecular dynamics simulations suggest that the differences for the longer polyproline peptides can be explained by chain bending, which considerably shortens the donor–acceptor distances.